2001
DOI: 10.1111/j.0014-3820.2001.tb00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Genetically Based Differentiation of Life-History Traits in the Perennial Shrub Lupinus Arboreus

Abstract: Abstract. Across large spatial scales, plants often exhibit genetically based differentiation in traits that allow adaptation to local sites. At smaller spatial scales, sharp boundaries between edaphic conditions also can create strong gradients in selection that counteract gene flow and result in local adaptation. Few studies, however, have examined the degree to which continuous populations of perennial plants exhibit genetically based differentiation in life-history traits over small spatial scales. We quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…A large geographic range enhances the breadth of bioclimatic variation a species encounters, and selection in response to such spatially continuous variation should result in trait autocorrelation among nearby populations (Murray, Brown, & Grace, 2003). On the other hand, large ecological amplitudes that allow a species to occupy distinct habitats may lead to local adaptation at small spatial scales (Hereford, 2009;Kittelson & Maron, 2001). Where distinct habitats occur repeatedly across a species' range, adaptation at large and small scales may occur simultaneously, yielding a pattern of continuous variation overlain by repeated occurrences of local adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…A large geographic range enhances the breadth of bioclimatic variation a species encounters, and selection in response to such spatially continuous variation should result in trait autocorrelation among nearby populations (Murray, Brown, & Grace, 2003). On the other hand, large ecological amplitudes that allow a species to occupy distinct habitats may lead to local adaptation at small spatial scales (Hereford, 2009;Kittelson & Maron, 2001). Where distinct habitats occur repeatedly across a species' range, adaptation at large and small scales may occur simultaneously, yielding a pattern of continuous variation overlain by repeated occurrences of local adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also noted an increase in genetic structure between earlier stages and later ones. Kittelson & Maron (2001) found an increase in genetic structure in Lupinus arboreus Sims between seeds and juveniles attributed to selection associated with adaptation to differing finescale environmental pressures between seed set and stand establishment. Cabin (1996) compared genetic diversity between the seed bank and juveniles in Lesquerella fendleri (A.Gray) S.Watson and found that the lack of structure in the seed bank was likely the result of the contribution from many overlapping generations.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to considering genetic structure in terms of spatial arrangement, examining individuals occurring in different cohorts and/or life stages could allow for detection of changes in genetic structure from class to class, potentially allowing for the inference of ecological and life history causes of this structure, which could then be applied to conservation programs (Kalisz et al 2001, Chung et al 2003a, Octavio-Aguilar et al 2017. Several studies have noted either a decrease (Hamrick et al 1993, Epperson & Alvarez-Buylla 1997, Parker et al 2001, Chung et al 2003a or an increase (Eguiarte et al 1992, Tonsor et al 1993, Cabin 1996, Kalisz et al 2001, Kittelson & Maron 2001, Chung et al 2005a, Jacquemyn et al 2006 in genetic structure as lifestages progress. A decrease in fine-scale genetic structure from seedlings to adults is generally explained by high mortality rates at early stages, while increases in genetic structure is explained by historical factors such as founder events and local selection, while isolation by distance processes (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the evolution of life-history strategies in seed plants have largely focused on traits associated with growth, survival, and reproduction (Gadgil and Solbrig 1972;Law et al 1977;Kittelson and Maron 2001). Less attention has been paid to the joint evolution of life-history strategies and reproductive systems (but see Zhang and Wang 1994;Morgan et al 1997;Pannell 1997a).…”
mentioning
confidence: 99%